The Role of Balinese Customary Law as a Social Institution for Immigrants and Tourists: Sanctions in Awig-Awig Against Krama Adat, Krama Tamiyu, and Tamiyu - Dewa Gede Edi Praditha (Istinbath : Jurnal Hukum, 2024)
The Balinese customary law is vital as a social institution regulating interactions between newcomers, tourists, and the local community. This research explores the sanctions embedded in the awig-awig (customary regulations) concerning three categories of society: krama adat (Indigenous community members), krama tamiyu (local residents), and tamiyu (newcomers/tourists). The study addresses numerous cases that have disrupted the societal balance, highlighting the need to examine the position of Balinese customary law in addressing such phenomena. Utilizing a sociolegal research method, this research reviews Bali Regional Regulation No. 4 of 2019 concerning Balinese Traditional Villages to conceptually assess the authority of traditional villages in enforcing these regulations towards indigenous communities and newcomers, coupled with the occurrences observed within society.